2013
DOI: 10.1111/ijsa.12024
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Cultural Intelligence in the Turkish Context

Abstract: The present article reports the results of two studies designed to evaluate the psychometric properties of the cultural intelligence (CI) scale in the Turkish context. The proposed four‐factor (cognitive, metacognitive, motivational, and behavioral) structure of CI was confirmed by confirmatory factor analysis. The results supported the discriminant validity of the four‐factor model of the CI scale in relation to the Big Five personality factors and the emotional intelligence factors. Furthermore, CI explained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 18 publications
7
22
0
6
Order By: Relevance
“…Results of the reliability analysis indicated that both the internal consistency and test–retest reliability estimates of CQS were adequate. These findings are consistent with those of other studies (Ang et al, ; Mahembe & Engelbrecht, ; Şahin et al, ; Shannon & Begley, ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Results of the reliability analysis indicated that both the internal consistency and test–retest reliability estimates of CQS were adequate. These findings are consistent with those of other studies (Ang et al, ; Mahembe & Engelbrecht, ; Şahin et al, ; Shannon & Begley, ).…”
Section: Discussionsupporting
confidence: 93%
“…As in the original model, CFA revealed a four‐factor structure. The four‐factor model was also consistent with results from the United States (Ang et al, ; Imai & Gelfand, ), Singapore (Ang et al, ), Turkey (Şahin et al, ), South Africa (Mahembe & Engelbrecht, ), Korea (Moon, ; Moon et al, ), and Iran (Khodadady & Ghahari, ). The second‐order CFA confirmed that the four CQ domains contributed to an overall CQ construct.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…What is more, the CQS has been validated in such diverse cultural contexts as Turkey (Şahin, Gürbüz, Köksal, & Ercan, 2013) and Iran (Khodadady & Ghahari, 2011). The instrument consists of 20 items divided into the four dimensions of cultural intelligence explained above.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%